Analisis Kelayakan Finansial Pengembangan Sistem Irigasi Cakram Otomatis Bertenaga Surya di Nusa Tenggara Barat - Popi Rejekiningrum; Satyanto Krido Saptomo (Balai Teknik Irigasi, 2015)
This study evaluates the result of implementation of water-efficient irrigation technology by using an automated roundshaped emitter, powered by solar cell. In order to determine investment feasibility of the automated system, Net Present Value (NPV), Internal Rate of Interest (IRR) and Benefit Cost Ratio (BCR) analysis have been conducted. An investment is feasible if the project fulfill the following criteria: (1) NPV is greater than zero, (2) IRR is greater than the discount rate which are applicable, (3) BCR greater than 1. The analysis shows that in general, the application of the automated system for mango, sugar apple, grapes, and chili plantation is very feasible. NPV of the investment ranges from Rp 1,533,423 to Rp 21,995,452; BCR value ranges from 1.337 to 3.775, and IRR value ranges from 17.38% to 34.10%. Implementation of the automated system for the development of mango and sugar apple plantation are the most feasible, with highest NPV, BCR and IRR. Whereas, implementation of the automated system for chili plantation is not feasible, since the value of NPV < 0, BCR < 1, and IRR < 14% interest rates. The average payback period of the automated system is about 4 year.